Process Analysis and Trial Tests for Hot-Rolled Stainless Steel/Carbon Steel Clad Plates - Chen, Z.Y.; Li, J.X.; Lin, Z.G.; Qi, J.J.; Sun, L.; Wang, G.D. (Проблемы прочности, 2019)
The trials of 304 stainless steel-clad plate made of plain Q345B carbon steel were performed on hot-rolling line of the Hesteel Group. After the two runs of pilot production, the key process parameters for the stainless steel/carbon steel clad plate were found to meet the GB/T 8165-2008 requirements. The interface shear strength of the clad plate was higher than 360 MPa, the yield strength of the final product was over 257 MPa, the clad plate tensile strength and elongation exceeded 351 MPa and 39.8%, respectively. The interpenetration of stainless steel and plain carbon steel layers was established to be complete, with the adequate composite interface. The tensile and shear properties of stainless steel-clad plates produced by the rolling process were at the same level as those obtained via the explosive method as an alternative, while their production cost were somewhat reduced.